Optical limiting applications of resonating plasmonic Au nanoparticles in a dielectric glass medium. (4th June 2021) - Kumar, Promod; Chandra Mathpal, Mohan; Jagannath, Gangareddy; Prakash, Jai; Maze, Jero-R; Roos, W D; Swart, H C
Abstract: Plasmonic nanostructures exhibiting high optical nonlinearities are widely used in the rapidly growing modern nanotechnology of nonlinear optics including biomedical applications due to their tunable plasmonic behavior. In this work, we investigate the nonlinear optical properties of uniformly distributed Au nanoparticles (NPs) embedded in pre-synthesized sodium−zinc borate glass by the well-known ion-exchange technique for optical limiting (OL) applications. Various techniques such as optical absorption spectroscopy, x-ray photoelectron spectroscopy, Transmission Electron Microscope (TEM), Photoluminescence, Time of Flight secondary mass spectroscopy and the Z scan technique were used for the characterization of these NPs. TEM confirmed spherically shaped Au NPs with varying sizes of up to 16 nm, in agreement with optical absorption spectroscopy. Nonlinear optical (NLO) properties of these Au NPs were investigated by using an open as well as close aperture Z scan technique which exhibited enhanced optical nonlinearities. The two-photon absorption (2PA) coefficients demonstrated an increasing trend while the OL threshold values demonstrated a decreasing trend as a function of heat treatment. The improved 2PA coefficients and decreased OL threshold values endorsed the Au NPs containing glasses as contending materials for the fabrication of promising optical limiters for the protection of eyes and other sensitive instruments from laser induced damages.